1993
DOI: 10.3109/10408419309113524
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Microorganisms

Abstract: This review followed from experiments suggesting that some fungi do not require calcium. It was found that many studies of a calcium requirement in microorganisms had assumed specificity for chelation agents such as EGTA and A23187, which the reagents did not possess. Early studies still cited today often preceded the recognition that microorganisms required manganese and zinc. As a result of both of these misunderstandings, there was rarely any attempt to replace calcium by other important trace elements. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
23
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 71 publications
4
23
0
Order By: Relevance
“…The intracellular free calcium ion concentration {[Ca 2ϩ ] i } is tightly regulated through Ca 2ϩ channels, Ca 2ϩ pumps, and Ca 2ϩ -binding proteins, and [Ca 2ϩ ] i is generally maintained in the nanomolar range. In bacteria, the role of Ca 2ϩ in cellular activities is less clear (3)(4)(5). It has been demonstrated that [Ca 2ϩ ] i is tightly regulated in some bacteria (6), and there is evidence indicating that calcium is critical to some bacterial cellular processes such as sporulation of Bacillus (7), chemotaxis of Escherichia coli (8), and heterocyst differentiation of cyanobacteria (9).…”
mentioning
confidence: 99%
“…The intracellular free calcium ion concentration {[Ca 2ϩ ] i } is tightly regulated through Ca 2ϩ channels, Ca 2ϩ pumps, and Ca 2ϩ -binding proteins, and [Ca 2ϩ ] i is generally maintained in the nanomolar range. In bacteria, the role of Ca 2ϩ in cellular activities is less clear (3)(4)(5). It has been demonstrated that [Ca 2ϩ ] i is tightly regulated in some bacteria (6), and there is evidence indicating that calcium is critical to some bacterial cellular processes such as sporulation of Bacillus (7), chemotaxis of Escherichia coli (8), and heterocyst differentiation of cyanobacteria (9).…”
mentioning
confidence: 99%
“…Among the best characterized of these entry pathways are the voltage-dependent Ca 2ϩ channels of the plasma membrane which open in response to membrane depolarization (3,9). Ca 2ϩ has been implicated in numerous processes of the budding yeast Saccharomyces cerevisiae (8,16,20,37), including stress-induced expression of ion transporter genes, bud formation, and viability upon pheromone-induced arrest. However, there is compelling evidence for a role for Ca 2ϩ in only the last of these processes (7,15,16,22).…”
mentioning
confidence: 99%
“…The DNA bands after polyacrylamide gel (6%) electrophoresis were visualized by x-ray films (Kodak). To confirm whether the sequence GTN 11 ACA in the ccbP promoter region was required for NtcA binding, EMSA was performed with two synthetic DNA fragments based on the DNA sequence from nucleotides Ϫ179 to Ϫ130 upstream of the start codon of the ccbP gene. The GTN 11 ACA sequence was changed to CCN 11 CCC in one of the fragments.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm whether the sequence GTN 11 ACA in the ccbP promoter region was required for NtcA binding, EMSA was performed with two synthetic DNA fragments based on the DNA sequence from nucleotides Ϫ179 to Ϫ130 upstream of the start codon of the ccbP gene. The GTN 11 ACA sequence was changed to CCN 11 CCC in one of the fragments. Coexpression of the ntcA of Anabaena 7120 and gfp was carried out by transformation of E. coli strain BL21(DE3) with pET-ntcA or pET-psaE (29), both of which confer resistance of ampicillin, and pPccbP-gfp, which contains the gfp gene under control of the ccbP promoter (10) and confers resistance to kanamycin, with selection on ampicillin and kanamycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation